Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Remaja tentang Lingkungan Sehat di Sekolah Menengah Pertama - Novita Elisabeth Daeli (LPPM STIKES Al-Ma'arif Baturaja, 2018)
Knowledge is the result of knowing and this happens after a person does sensing of a particular object. Adolescence is a developmental period of transition between childhood and adulthood that includes biological, cognitive, and socio-emotional changes. The adolescent environment is closely related to the school's confusion. Knowledge of a healthy environment can increase through health education. This researched aims to understand determine of effect health education on increasing adolescents' knowledge about a healthy environment in school. in this research, there are 80 respondents will be used as samples by applying the total sampling technique. The research design used quantitative research with a cross-sectional analysis. The research instrument is a questionnaire about healthy environment knowledge. This research was conducted in May 2014. The result of bivariate analysis using the Wilcoxon signed-rank test with a degree of significance α (0.05). The results showed that there was a significant effect of health education between before and after health education with a p-value <0.0001. Based on this research, the researcher suggests that to improve the better knowledge of adolescent teenagers should be done health counseling to schools health cadres and community nurses.